Metamorphosis of EduX: a comparative study for education in the metaverse - Lataifeh, Mohammad; Ahmed, Naveed (Frontiers in Computer Science, 2024)
This research explores critical aspects of the ongoing educational transition from traditional twodimensional digital platforms toward immersive realities in the metaverse. In this work, a networked, collaborative, ubiquitous, and immersive platform, "EduX" is developed to host different educational sessions. Several metrics are tracked and compared with parallel sessions using traditional digital platforms used by educational institutions, particularly during and after the Covid-19 pandemic, such as Zoom, MS Teams, and Black Board Ultra as the Learning Management System. Four groups of students from different domains of knowledge (n=396) participated in the study, whereby each group was split into two subgroups, taking their session via EduX and BBUltra, followed by postassessments and discussions. Using a mixed methods approach, quantitative and qualitative data were collected and analyzed to examine the influence of the platform on engagement, performance, and overall student achievements. The discussed results demonstrate superior usability and user experience levels of the proposed platform, with higher levels of engagement, leading to significantly improved attainments. Other than demonstrating the efficacy and feasibility of the platform, this work establishes fundamental metrics to be considered by software and hardware solution providers, academic institutions, and the research community concerned with the convergence towards immersive technologies.